ABOUT INFLUENCE OF CONVECTIVE MELT FLOWS ON INGOT HARDENING AT HORIZONTAL CONTINUOUS CASTING - E. B. Demchenko (Наука и техника)
The paper proposes a methodology for evaluation of convective melt flow influence on ingot hardening at horizontal continuous casting that permits to calculate critical flow rates being sufficient for starting skin melt.Due to investigation of ingot formation process using method of hydrothermal analogy it has become possible to reveal a picture of the convective melt movement along hardening front and determine real flow rates.Comparison of calculative and real flow rates has permitted to detect zones of hardening front subjected to melting.The paper shows that application of a partitioning device in the process of horizontal casting significantly decreases an influence of convective melt flows on ingot hardening.